First assessment of anthropogenic marine debris in the Cut Mamplam Mangrove Ecosystem, Lhokseumawe City - Hayatun Nufus; Rika Astuti; Roni Arif Munandar; Fitra Wira Hadinata; Syahrial Syahrial; Ekamaida Ekamaida; Muhammad Fauzan Isma; Haqqy Rerian Erlangga; Nella Tri Agustini (Universitas Malikussaleh, 2025)
This study aimed to determine the presence of AMD, analyze mangrove structure, and determine the relationship between AMD and mangrove density. AMD and mangrove stands were collected using a 40 meter transect line parallel to the shoreline, and four 10 x 10 m plots were created. One-way ANOVA statistics were used to test the mean differences in SLA telling, while the Shapiro-Wilk test and Spearman correlation were performed to analyze the relationship between SLA telling and mangrove structure. A total of 11923 AMD items were found in the Cut Mamplam mangrove ecosystem, with a density ranging from 47075 to 76900 items/ha. Furthermore, four species of mangrove trees were found in the mangrove stands, with Avicennia alba having the highest tree, sapling, and seedling densities (3275 ± 5158 ind/ha, 2800 ± 1932.18 ind/ha, and 132500 ± 75883.68 ind/ha). The relationship between AMD and mangrove density was not very strong, with no significant associations between adults, saplings, or seedlings (p > 0.05) on the amount of AMD retained in the Cut Mamplam mangrove ecosystem. This study is an initial step in assessing the impact of AMD on mangrove vegetation and sustainable monitoring, leading to the initiation of public awareness and future strategies for improved coastal and marine monitoring and management. Keywords: Cut Mamplam; Density; Plastic; Pollution; Reporting